An improved integer coded genetic algorithm for security constrained unit commitment problem - Golestani, S.; Raoofat, M.; Farjah, E. (2008 IEEE 2nd International Power and Energy Conference, 2008)
This paper presents a novel approach to solve the security constrained unit commitment problem using decomposition technique. The method applies an improved integer coded genetic algorithm (ICGA) to schedule the commitment states of units. ICGA technique reduces the size of chromosomes and computation time significantly. Here, the proposed ICGA has been enhanced by using perturbation operator. Simulation results for six-bus test system exhibit the effectiveness of the proposed approach.